Customer value creation via business model implementation - Andreas, Karaoulanis (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
Business models are the blueprints upon which the whole structure and operation of the company is based. The aim of this paper is to underline the importance of business models in value creation for the company and to dig a bit deeper by revealing the synthesis of an abstract business model concept. The importance of customer value proposition via the customer value creation is very well underlined in order to pinpoint the authors prevalent idea that focusing on customersneeds should be the alpha and the omega for the eurythmic operation of every contemporary company.